SOCIOLINGUISTICS AND UNDERSTANDING LANGUAGE IN SOCIAL CONTEXTS (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
ociolinguistics is the study of the relationship between language and society, exploring how social factors such as class, gender, ethnicity, age, and context influence language use. This article examines key concepts in sociolinguistics, including language variation, code-switching, diglossia, and the role of language in power dynamics and identity formation. It highlights how language varies across different social groups and settings and how these variations reflect and perpetuate societal structures. T